Narcolepsy and excessive daytime sleepiness - Zeman, A; Britton, T; Douglas, N; Hansen, A; Hicks, J; Howard, R; Meredith, A; Smith, I; Stores, G; Wilson, S; Zaiwalla, Z (2004)
Excessive daytime sleepiness is common,1 yet opportunities to learn about sleep medicine in medical school are rare; a survey in 1998 indicated that undergraduate courses devoted a median of five minutes to sleep and its disorders.2 In this review we provide an update on the biology, diagnosis, and management of narcolepsy—an important, yet often misdiagnosed, cause of sleepiness that has seen exciting recent advances. We also briefly outline the other principal causes of daytime sleepiness and aim to equip the general reader with a practical approach to the assessment of patients who complain of excessive daytime sleepiness.